PENGARUH MEDIA KOMIK DALAM MENINGKATKAN KEMAMPUAN MENULIS TEKS NEGOSIASI PADA SISWA KELAS X SMA SANTU PETRUS SIDIKALANG - pratiwi novita tinambunan (Jurnal Bahastra, 2021)
ABSTRACT This study aims to determine the effect of comic media in improving the ability to write negotiating texts. This research was conducted at SMA Santu Petrus Sidikalang. The method used in this research is an experimental method, which is a method or media that reveals clear facts with the Static Group Comparison design. The population of this study were all students of class X SMA Santu Petrus Sidikalang which consisted of 3 classes with a total of 105 people. The sampling technique used was simple random sampling. The sample of this study was 60 students of class XMIA1 and XMIA2. The instrument used in collection the data was essay-test in the form of an assignment, namely writing a negotiation text. Hypothesis testing is done using the "t". The findings in this study indicate that the students' ability in writing negotiating texts before using comic strips was in the sufficient category with an average score of 72,4. Meanwhile, after using comic media, it is in the good category with an average score of 84. Continuing to test the hypothesis, it shows that the Hhitung t table is 8,46 2.00 at the significant level α = 0.05 or 5%. Thus, it is proven that the alternative hypothesis (Ha) is accepted and it can be stated that the comic media influences the students' ability in writing negotiating texts by the tenth grade students of SMA Santu Petrus Sidikalang. Key words: Writing Negotiation Text, Comic Media.